Possession and its effect on ownership - Al-Hamziya, Muftah Faraj Abdel Samie (Al-Mukhtar Journal of Social Sciences, 2026)
Possession is one of the important matters that need more research because of its impact on people's ownership. Thus, this research aims to study this term by clarifying its concept and effect on the transfer of ownership, along with mentioning the period affecting it, and listing the sayings of the Fish jurists with their evidence, as well as the widely accepted opinion. The research discusses the matters that make the right holder claims his right even after the period has passed. The most important point in this research is to link it to Law No. 123 of 1970 AD regarding the disposal of agricultural and reclaimed lands owned by the state of the Revolutionary Command Council at the time. It enabled the beneficiaries to own these lands, deprived their owners of it, and demonstrated its violation of the Sharia.
Keywords: Possession; ownership; Revolutionary Command Council